KRAS (G12D) Cooperates with AML1/ETO to Initiate a Mouse Model Mimicking Human Acute Myeloid Leukemia - Shanmin Zhao; Yuxia Zhang; Kun Sha; Qiu Tang; Xiaohua Yang; Chenlin Yu; Zhixue Liu; Wei Sun; Liping Cai; Chen Xu; Shufang Cui (Cellular Physiology and Biochemistry, 2014)
Background/Aims: It has been demonstrated that KRAS mutations represent about 90% of cancer-associated mutations, and that KRAS mutations play an essential role in neoplastic transformation. Cancer-associated RAS mutations occur frequently in acute myeloid leukemia (AML), suggesting a functional role for Ras in leukemogenesis. Methods: We successfully established a mouse model of human leukemia by transplanting bone marrow cells co-transfected with the K-ras (G12D) mutation and AML1/ETO fusion protein. Results: Mice transplanted with AML/ETO+KRAS co-transduced cells had the highest mortality rate than mice transplanted with AML/ETO- or KRAS-transduced cells (115d vs. 150d). Upon reaching a terminal disease stage, EGFP-positive cells dominated their spleen, lymph nodes, peripheral blood and central nervous system tissue. Immunophenotyping, cytologic analyses revealed that AML/ETO+KRAS leukemias predominantly contained immature myeloid precursors (EGFP+/c-Kit+/Mac-1-/Gr-1-). Histologic analyses revealed that massive leukemic infiltrations were closely packed in dense sheets that effaced the normal architecture of spleen and thymus in mice transplanted with AML1/ETO + KRAS co-transduced cells. K-ras mRNA and protein expression were upregulated in bone marrow cells of the K-ras group and AML1/ETO + Kras group. The phosphorylation of MEK/ERK was significantly enhanced in the AML1/ETO + Kras group. The similar results of the AML1/ETO + Nras group were consistent with those reported previously. Conclusion: Co-transduction of KrasG12D and AML1/ETO induces acute monoblastic leukemia. Since expression of mutant K-ras alone was insufficient to induce leukemia, this model may be useful for investigating the multi-step leukemogenesis model of human leukemia.